Pendidikan Sosial Berbasis Tauhid dalam perspektif Al-Qur’an - Muhammad Khoiruddin (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2018)
Abstract: The holy quran has many perspectives and some of them relates to social educations and pradigms of socio-humanity. As in the meaning, quran has relation between men with God (habl min Allah) and men with men (habl ma’a al-nas), which are already popular and understood among the men. There are two issues that need among various relevant parties in practice of in the islamic education to supply many dimensions of dialectics horizontally and dimension of submission vertically. Horizontally, both social education and evidence of oneness should be able to develop reality of the life. Vertically, education called social and evidence of the oneness based provide an instrument for charge with the care of, capitalize on the fact, and preserve narural resource. These become a way to understand phenomena and honeybee in their effort to attain intercourse life to the creator. Keywords : Tawheed, Social, Humanis, Education